Application of Problem-based Learning Assisted by Decision Maker Application on Computational Thinking Materials to Improve Student Learning Outcomes at SMP Negeri 2 Gemolong Sragen Regency - Indriyanto Tri Wardoyo; Basori Basori; Astika Wulansari (Journal of Informatics and Vocational Education, 2023)
This research is a classroom action research, which aims to improve student learning outcomes in the informatics subject matter of computational thinking. This study applies Problem-based learning assisted by decision-makers on smartphones. Students are directed to download and install the decision-maker application on their smartphones. Then students use the information in the application as a reference for information as material for discussion with their respective groups. From the results of the summative assessment, the data showed an increase in the average value of learning outcomes in each cycle.